A case study of selected bars used by Gen Zs in relation to the application of third places - Antonio, Allyson A.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines, 2023)
The study examined the application of the characteristics in Oldenburg's Third Place Theory that had an influence on Gen Z Filipinos in selected Poblacion bars. Thus, the study identified interior design features that attracted Gen Z Filipinos to bars for socialization and evaluated their preferred characteristics of third places. The research included seven (7) Gen Z Filipinos and 3 selected bars from Poblacion, Makati. The research followed a deductive approach and conducted a quantitative descriptive case study. The sample bars were selected based on location, accessibility and availability of photos online, whereas respondents were selected based on age and past experience of using bars as a space for socialization. Data was collected through an online questionnaire that analyzed responses using a Likert Scale and an online interview for thematic analysis. Based on the findings, the common interior design features that encourage Gen Z Filipinos to visit bars for socialization included lighting, cleanliness, ceiling height, interior area, display shelves, colors, floor and wall finishes, furniture, and select decoration within the interiors. From this, the identified preferred third place characteristics among Gen Z Filipinos, included the characteristics of Low Profile, Home-away-from Home, Ease of Access, and Neutral Ground. These were consistently ranked first among the bar respondents would most likely visit for socialization. These interior design features and the related third place characteristics encouraged respondents to socialize in bars. Future research may consider expanding to other local bars and researching larger samples to generate statistical data for generalizations.
Thesis
Includes bibliographical references (pages 104-109)
Keywords: Bars (Drinking establishments) -- Decoration -- Philippines; Generation Z -- Philippines